Direct numerical simulation of homogeneous isotropic cross-helical mhd turbulence - Titov, Valeriy Viktorovich (Computational Continuum Mechanics, 2019)
Magnetohydrodynamic (MHD) turbulence with cross-helicity excited by a large-scale source is considered. The source is a random external force contributing energy with a controlled level of cross-helicity. The proposed approach allows one to form and maintain high levels of cross-helicity without using an external constant magnetic field. The force is implemented in the software package TARANG. A series of numerical experiments with a constant energy flow and various levels of injection of cross-helicity have been carried out. The ratio of the cross-helicity to the total energy varied in the range from 0 to 0.6. The calculations were carried out at kinetic Reynolds number R = 2094 and at magnetic Prandtl number Prm= 1 on the grid 5123. An equal amount of energy per unit of time was introduced into velocity and magnetic induction fields. Regardless of the level of cross-helicity, the rate of dissipation of magnetic energy has always been higher than the intensity of injection. Spectral energy fluxes indicated a positive energy flux from the velocity field to the magnetic induction field. The high levels of cross helicity led to energy accumulation on a large scale and to changes in energy distribution over the scale. The spectral energy densities in the Elsasser variables z±showed a significant difference in the slopes of the z+and z-spectra. On the spectral flux z-, a region close to the inertia interval was detected. Qualitative agreement with the results obtained earlier using cascade models is shown. Varying the ratio of codirectional change of fields did not affect the integral and spectral characteristics of the flow. The results obtained allow us to use the proposed force for a detailed study of the evolution of homogeneous isotropic turbulence with a high level of cross-helicity and its dissipation.
Keywords: direct numerical simulation; magnetohydrodynamics; cross-helicity; turbulence; pseudospectral method; TARANG code